Microwave-Assisted Green Synthesis of Pure and Mn-Doped ZnO Nanocomposites: In Vitro Antibacterial Assay and Photodegradation of Methylene Blue - Khan, Sher Bahadar; Khan, Muhammad Iqbal; Nisar, Jamila (Frontiers in Materials, 2022)
This paper describes the eco-friendly microwave-assisted green synthesis of pure and manganese doped zinc oxide nanocomposites using ethanolic solution of castor oil as a reductant and capping agent. Solutions of Zn2+ and Mn2+ ions were mixed in fixed ratios to obtain 0%, 1%, 2.5%, 5% and 7% pure and Mn-doped ZnO nanomaterials. The obtained nanomaterials were characterized by powder XRD, FT-IR spectroscopy, scanning electron microscopy and EDX analyses. Powder XRD furnished characteristic fragmentation patterns for the confirmation of the synthesized materials and was also used to estimate the size of the synthesized nanoparticles by Scherrer’s equation. Diffraction patterns were characteristic of wurtzite structure and of the size in the range of 6.5, 5.6, 5.2, 5.1 and 4.3 nm for pure and Mn-doped ZnO nanocomposites. Electronic spectra displayed maximum absorbance at 340 nm and manganese doping caused a red shift. FT-IR spectra confirmed that the formation of zinc oxide nanoparticles as Zn─O appeared at below 700 cm−1, as well as the presence of organic moieties of the castor oil acting as stabilizing ligands. Scanning electron micrographs revealed all the synthesized materials were spherical in shape with some aggregation and polydispersity; while in the EDX spectra, specific peaks with characteristic patterns were seen for Zn, O and Mn. Photocatalytic degradation of Methylene Blue (MB) was checked in the presence of sunlight and in dark. Interestingly, samples placed under the solar radiation exhibited significant results only the with the catalyst, all the samples used without catalyst showed negligible degradation effects even the samples placed in the dark containing catalysts also displayed negative effect. A mechanism for this significant activity has also been proposed. In vitro the anti-bacterial potential was studied against two pathogenic strains i.e. Streptococcus aureus and Escherichia coli; interestingly activity kept on increasing with the increasing manganese content; overall, the all the samples presented comparable activity to ciprofloxacin.